The wet and stormy UK winter of 2019/2020. (4th May 2021) - Davies, Paul A.; McCarthy, Mark; Christidis, Nikos; Dunstone, Nick; Fereday, David; Kendon, Mike; Knight, Jeff R.; Scaife, Adam A.; Sexton, David
Abstract : During the winter of 2019/2020, the UK experienced its fifth wettest of any calendar month on record during what was the wettest February on record. In this paper we review the predictable component of the winter situation, the role of climate variability and show that climate change has increased the likelihood of extremes of this nature.